TANGGUNGJAWAB YURIDIS BAGI PELAKU PEMBUNUHAN DIBAWAH PENGARUH MINUMAN ALKOHOL - Budi Arifin (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTOne of the crimes committed by the community is a crime of murder. Crime The murder is one of deviant behavior which is in essence contrary to legal norms and religious norms and is harmful to people's livelihoods and lives. In the crime of murder, the target of the offender is the life of someone who cannot be replaced with anything. In this case, someone's unconsciousness due to drunkenness due to alcoholism (alcohol) must be more closely watched to how severe the level of unconsciousness of the person. Because lately there have been a lot of reports in the mass media of criminal acts of murder and other criminal acts caused by drunkenness. It becomes a problem of how to judge a person's actions carried out in a drunken state. Regarding some examples of criminal cases of murder committed by drunk people, it is very difficult to determine exactly the criminal liability.Based on the results of the study it can be concluded that the state of drunkenness is not formulated in the imposition of criminal charges because in consideration of the drunken state judge is only used as an element of information, criminal convictions decided by the judge only focus on the articles stipulated in the Criminal Code so that drunkenness here is not considered reason for being unable to be responsible / reason for the inability to be responsible which can be sentenced separately, mentioned in article 40 of the KUHP concept regarding "people suffering from mental disorders". In this case, the state of drunkenness can be classified into the article. Medically drunk people can be categorized as psychologically disturbed even though this does not happen permanently, in other words, mental disorders that occur are temporary. Because when the effects of alcohol are gone, they are always sane and legal sanctions against the perpetrators of murder under the influence of alcoholic beverages can be snared with article 338 of the Criminal Code: "whoever deliberately seizes the lives of others, is threatened with murder with fifteen prison sentences year". The article can be applied because the drunken state is only used as an element of information. Keywords: murder, alcoholic drinks